Epignathus, hypolastic left heart syndrome, and trisomy 18 in a small for gestational age female twin - S. Rugolotto; A. Bertolini; I. Cogo; A. Pietrobelli; S. Pecori; M. Furlani; E.M. Padovani (PAGEPress Publications, 2013)
We describe a rare association of hypoplastic left heart syndrome, trismony 18, and epignathus in a 970 g female twin born at 37 weeks of gestational age. She died at 24 hours of age. Neonatologists and obstetricians should be aware of this rare association for a thorough prenatal counselling.